2022
DOI: 10.1523/jneurosci.2044-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sleep in Formation of Relational Associative Memory

Abstract: Relational memory, the ability to make and remember associations between objects, is an essential component of mammalian reasoning. In relational memory tasks, it has been shown that periods of offline processing, such as sleep, are critical to making indirect associations. To understand biophysical mechanisms behind the role of sleep in improving relational memory, we developed a model of the thalamocortical network to test how slow-wave sleep affects performance on an unordered relational memory task. First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Paired associative learning (PAL) has previously shown to be sensitive to the effect of sleep 1 , 40 , 77 79 . We adapted the task for participants to make it relatively short (20 min for the learning phase, 5–10 min for the retrieval phase), and based on visual stimuli (vPAL; see also ref.…”
Section: Methodsmentioning
confidence: 99%
“…Paired associative learning (PAL) has previously shown to be sensitive to the effect of sleep 1 , 40 , 77 79 . We adapted the task for participants to make it relatively short (20 min for the learning phase, 5–10 min for the retrieval phase), and based on visual stimuli (vPAL; see also ref.…”
Section: Methodsmentioning
confidence: 99%
“…All statistical comparisons were carried out using the Pingouin Python package for statistical analysis 66 . All correlations reported are Pearson correlations unless stated otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…Paired associative learning (PAL) had been previously proven sensitive to the effect of sleep [65][66][67][68][69] and especially familiarity was previously shown to be sensitive to pathological aging 24,25 .…”
Section: Memory Assessmentmentioning
confidence: 99%
“…Participants who received sufficient nocturnal sleep after training gained better insights about hidden rules than participants who were forced to stay awake [33]. A recent thalamocortical network model-based report suggested that awake learning was replayed in slow waves of NREM, leading to drawing indirect associations within a transitive inference task, and a correlation was present between the number of slow waves and the improvement in forming the associations [44]. Additionally, a recent study on both humans and rodents revealed that awake hippocampal coactivations, specifically during sharp wave ripples, represent a mnemonic shortcut for nesting inference relationships [45].…”
Section: Idling As a Substrate For Creative Cognitive Supremacymentioning
confidence: 99%